Exploring the Relationships Between Grit, Self-Efficacy, and Academic Stress in Indonesian Islamic Boarding High School Students - Novia Eka Pratiwi; Herdian Herdian; Tri Na’imah; Fatin Rormah Nur Wahidah (Research and Innovation in Social Science Education Journal (RISSEJ), 2023)
This research employs a quantitative approach to investigate the relationships among Age, Grit, Self Efficacy, and Academic Stress. The study ensures ethical compliance by obtaining participants' informed consent and employing offline data collection through structured questionnaires. A diverse sample is drawn from the Student of Islamic Boarding senior high School Banyumas, Indonesia, using the simple random sampling method. A total of 115 participants, predominantly female (69.6%), with a mean age of 17 years (40.0%), contributed to the study. The Student-Life-Stress Inventory (SSI) Scale, Grit-S Scale, and General Self-Efficacy Scale are used to measure the variables. Results reveal no significant differences between sex groups regarding Grit, Academic Stress, and Self Efficacy scores (all p-values > 0.05). The correlation matrix underscores non-significant associations between variables, emphasizing the absence of strong linear relationships. These findings highlight the need for an in-depth exploration of additional factors influencing academic stress experiences and call for more comprehensive research designs to unravel the intricate dynamics shaping student well-being.